Dual Mobility Total Hip Arthroplasty is not Associated with a Greater Incidence of Groin Pain in Comparison with Conventional Total Hip Arthroplasty and Hip Resurfacing: A Retrospective Comparative Study. Issue 2 (December 2020) - Stavrakis, Alexandra I.; Khoshbin, Amir; Joseph, Amethia; Lee, Lily Y.; Bostrom, Mathias P.; Westrich, Geoffrey H.; McLawhorn, Alexander S.
Background: Groin pain is a common long-term complication of total hip arthroplasty (THA). Femoral head size has been proposed as one of the primary causes. The implants used in dual mobility (DM) THA have large outer-bearing articulations, which could increase the risk of post-operative groin pain. Hip resurfacing (HR), too, has been shown to be associated with a risk of groin pain. Questions/Purposes: The goals of this study were to compare the incidence of groin pain at 1 year after hip arthroplasty in patients with different femoral head diameters and in patients undergoing conventional THA, DM THA, and HR. Methods: After combing an institutional registry for all patients who had undergone THA or HR for primary hip osteoarthritis, we included 3193 patients in the analysis; 2008 underwent conventional THA, 416 underwent DM THA, and 769 underwent HR. We used logistic regression modeling to analyze the relation of groin pain at 1 year after surgery to patient demographics and clinical characteristics, including age, sex, body mass index (BMI), University of California at Los Angeles activity score at 1 year after surgery, bearing couple, and the ratio of acetabular diameter to femoral head diameter. We also measured cup inclination and anteversion in a subset of patients with and without groin pain at 1 year to assess whether pain could be related to implant position. Results: Overall, 8.7% of patients reported groin pain at 1 year. Patients with groin pain were younger and had lower BMIs. There were increased odds of groin pain with a greater cup-to-head ratio, although DM implants, interestingly, were not significantly associated with groin pain; this may be attributable to so much of their movement taking place inside the implant. Subgroup analysis measuring cup inclination and anteversion showed no difference in cup position between patients with and without pain. Conclusion: In this population of hip arthroplasty patients, the incidence of groin pain 1 year after surgery did not differ among patients undergoing DM and conventional THA; DM THA in particular was not associated with a higher risk of groin pain, despite its comparatively larger femoral head sizes. HR, on the other hand, was associated with a higher risk of pain. Appropriate implant sizing and bearing couple choice may optimize the functional benefit of THA.